(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Evaluate the relationship between stress level, sleep quality, quality of life and changes in FSH, LH, prolactin hormone levels with the results of treatment of severe acne vulgaris in female patients with isotretinoin. Research subjects and methods: Clinical trial, prospective, comparing results before and after 3 months of severe acne vulgaris treatment on 45 female patients with isotretinoin 20 mg/day at the National Dermatology Hospital from October 2022 to September 2023. Results: After 3 months of treatment, DASS21 score decreased from 13±12 to 11±12, P<0.01; PSQI score decreased from 5.36±3.17 to 4.71±1.84, P=0,04; DSQI score decreased from 7±5 to 4.64±2.6, P<0.01. There is a moderate positive relationship between stress level (r=0.48; P<0.01) and quality of life (r=0.34; P<0.01) with treatment results. There is no relationship between sleep quality and changes in FSH, LH, prolactin levels and treatment results. Conclusion: Taking isotretinoin 20 mg/day helps reduce stress levels, improve sleep quality, and improve quality of life for female patients with severe acne vulgaris after 3 months of treatment.